Unresolved issues in the diagnosis and management of thrombotic antiphospholipid syndrome - Deepa J. Arachchillage; Mike Laffan (Research and Practice in Thrombosis and Haemostasis)
Antiphospholipid syndrome (APS) is a highly prothrombotic autoimmune disease characterized by the persistent presence of antiphospholipid autoantibodies (aPL) in association with thrombotic or nonthrombotic macro- and microvascular manifestations and/or pregnancy complications. This review is restricted to thrombotic APS. Since the publication of the American College of Rheumatology/European Alliance of Associations for Rheumatology classification criteria for APS, several authors have emphasized the difference between “classification” and “diagnosis” as a potential pitfall for clinicians. In addition to challenges associated with the diagnosis of APS, there are many unresolved areas in understanding pathogenesis and in the management of both thrombotic and obstetric APS. Although APS is an antibody-mediated autoimmune disease, secondary thrombosis prevention is achieved by anticoagulation, mainly with vitamin K antagonists, such as warfarin, rather than immunomodulation. Evidence is convincing for the use of vitamin K antagonists in triple-positive APS with venous thromboembolism. However, the best anticoagulant approach in the management of venous thromboembolism patients with single or dual positive aPL is not clear. Management of patients with stroke or arterial thrombosis with aPL remains a major unresolved issue, although some guidelines recommend the use of warfarin rather than antiplatelet therapy as the first-line treatment of stroke in APS. Recurrent thrombosis, despite therapeutic anticoagulation, remains a frequent problem and may be explained by the contribution of thrombo-inflammation in patients with thrombotic APS. In this narrative review, we discuss some of the unresolved issues in the diagnosis and management of thrombotic APS.